Genomic organization, sequence divergence, and recombination of feline immunodeficiency virus from lions in the wild - Sondgeroth Kerry (BMC Genomics, 2008)
Abstract Background Feline immunodeficiency virus (FIV) naturally infects multiple species of cat and is related to human immunodeficiency virus in humans. FIV infection causes AIDS-like disease and mortality in the domestic cat (Felis catus) and serves as a natural model for HIV infection in humans. In African lions (Panthera leo) and other exotic felid species, disease etiology introduced by FIV infection are less clear, but recent studies indicate that FIV causes moderate to severe CD4 depletion. Results In this study, comparative genomic methods are used to evaluate the full proviral genome of two geographically distinct FIV subtypes isolated from free-ranging lions. Genome organization of FIVPle subtype B (9891 bp) from lions in the Serengeti National Park in Tanzania and FIVPle subtype E (9899 bp) isolated from lions in the Okavango Delta in Botswana, both resemble FIV genome sequence from puma, Pallas cat and domestic cat across 5' LTR, gag, pol, vif, orfA, env, rev and 3'LTR regions. Comparative analyses of available full-length FIV consisting of subtypes A, B and C from FIVFca, Pallas cat FIVOma and two puma FIVPco subtypes A and B recapitulate the species-specific monophyly of FIV marked by high levels of genetic diversity both within and between species. Across all FIVPle gene regions except env, lion subtypes B and E are monophyletic, and marginally more similar to Pallas cat FIVOma than to other FIV. Sequence analyses indicate the SU and TM regions of env vary substantially between subtypes, with FIVPle subtype E more related to domestic cat FIVFca than to FIVPle subtype B and FIVOma likely reflecting recombination between strains in the wild. Conclusion This study demonstrates the necessity of whole-genome analysis to complement population/gene-based studies, which are of limited utility in uncovering complex events such as recombination that may lead to functional differences in virulence and pathogenicity. These full-length lion lentiviruses are integral to the advancement of comparative genomics of human pathogens, as well as emerging disease in wild populations of endangered species.